Pengaruh Pengeluaran Pemerintah Sektor Kesehatan, Pertumbuhan Ekonomi, Dan Kemiskinan Terhadap Indeks Pembangunan Manusia (Kabupaten/Kota Di Provinsi NTB) - Apriska, Lita; Irwan, M.; Suprapti, Ida Ayu Putri; Anggara, Jaka (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the effect of government spending on the health sector, economic growth and poverty on the human development index. The population used in this study is 10 regencies / cities in West Nusa Tenggara Province for the last 10 years. The data collection method used is the sample survey method. The data analysis method in this study uses panel data regression processed using the Eviews 10 application. The results of the analysis in this study are Partially government spending in the health sector has a positive and significant effect on the human development index, economic growth has a positif and significant effect on the human development index and poverty has a negative and significant effect on the human development index. While simultaneously government spending in the health sector, economic growth and poverty have a significant effect on the human development index